Ptch2 is a Potential Regulator of Mesenchymal Stem Cells - Juuri, Emma; Tikka, Pauli; Domanskyi, Andrii; Corfe, Ian; Morita, Wataru; Mckinnon, Peter J.; Jandova, Nela; Balic, Anamaria (Frontiers in Physiology, 2022)
Ptch receptors 1 and 2 mediate Hedgehog signaling pivotal for organ development and homeostasis. In contrast to embryonic lethal Ptch1−/− phenotype, Ptch2−/− mice display no effect on gross phenotype. In this brief report, we provide evidence of changes in the putative incisor mesenchymal stem cell (MSC) niches that contribute to accelerated incisor growth, as well as intriguing changes in the bones and skin which suggest a role for Ptch2 in the regulation of MSCs and their regenerative potential. We employed histological, immunostaining, and computed tomography (µCT) analyses to analyze morphological differences between Ptch2−/− and wild-type incisors, long bones, and skins. In vitro CFU and differentiation assays were used to demonstrate the MSC content and differentiation potential of Ptch2−/− bone marrow stromal cells. Wound healing assay was performed in vivo and in vitro on 8-week-old mice to assess the effect of Ptch2 on the wound closure. Loss of Ptch2 causes increases in the number of putative MSCs in the continuously growing incisor, associated with increased vascularization observed in the tooth mesenchyme and the neurovascular bundle. Increased length and volume of Ptch2−/− bones is linked with the increased number and augmented in vitro differentiation potential of MSCs in the bone marrow. Dynamic changes in the Ptch2−/− skin thickness relate to changes in the mesenchymal compartment and impact the wound closure potential. The effects of Ptch2 abrogation on the postnatal MSCs suggest a crucial role for Ptch2 in Hedgehog signaling regulation of the organ regenerative potential.